Molecular modelling of berberine derivatives as inhibitors of oncogenic signalling pathways in breast cancer cell lines - Kaboli, Parham Jabbarzadeh (2017)
Berberine (BBR) is an alkaloid that is widely distributed in different plant species. Several studies have been carried out on the anti-cancer effects of BBR but direct targets of BBR are unknown. In the development of approximately 20-25% of all cancers, altered hedgehog (Hh) signalling is involved where the smoothened (Smo) transmembrane receptor triggers Hh signalling pathway towards Gli1 gene expression. Besides Smo receptor, BRAF mutations have been also detected in 7% of all cancers and 66% of melanomas; as such, the FDA has approved a few BRAF inhibitor drugs to date. However, BRAF can activate CRAF leading to resistance to BRAF inhibitors. The aim of this study is to model and compare the effects of BBR against key proteins involved in Hedgehog, MAP kinase, and PI3K pathways using in silico and in vitro approaches. BBR is found to interact with Lys395 of Smo receptor via hydrogen bonding and cation-π interactions [Score= -8.72 kcal/mol (Smo)]. In addition, π-π interactions between BBR aromatic rings and two aromatic residues in the Smo transmembrane domain, Tyr394 and Phe484, are noted. Target specific binding efficiency indices using an in-silico approach are calculated to plot the Smo-specific binding potency of each ligand. In addition, interactions of BBR derivatives (total number= 485 derivatives) against BRAF and CRAF kinases are modelled and predicted using an in silico-based approach. The Adenosine Triphosphate (ATP) is modelled in order to analyse and identify the residues important in BRAF docking. Results show Lys483 and Asp594 are the most important residues involved in both ATP and BBR binding [Scores= -11.50 kcal/mol (ATP); -8.50 kcal/mol (BBR)]. In addition to these polar residues, Trp530 and Phe583 are also applicable to the molecular docking of BRAF. The Asp593 is excluded from the enzyme cavity, while Phe594 is included inside the cavity, making the enzyme inactive. Finally, three alternatives for BBR are identified with dual RAF inhibition effects. Direct effects of BBR derivatives against BRAF and CRAF kinases have not yet been reported previously, and thus, for the first time, three protoberberines are reported as lead compounds against RAF kinases [BBR-7 (Score= - 9.75 kcal/mol), BBR-9 (Score= -9.76 kcal/mol), and BBR-10 (Score= - 9.27 kcal/mol)]. In the current study, molecular docking and molecular dynamics simulations are also used for EGFR, p38 MAPK, ERK1/2 and AKT. The effects of BBR on MAP kinase and PI3K pathways are evaluated using Immuno-florescence assays and the amounts of phosphorylated kinases are compared with total kinases after they are treated with different concentrations of BBR [IC50s= 7μM (EGFR), 45μM (ERK1/2), 60μM (AKT), 75μM (p38)]. BBR interacts accurately with EGFR, AKT, P38, and ERK1/2 active sites in silico, and decreases the level of active forms of corresponding enzymes in studied cell lines [Scores= -7.22 kcal/mol (EGFR), -7.51 kcal/mol (ERK), -7.78kcal/mol (AKT), -7.42 kcal/mol (p38)]. In addition, it is observed that BBR has toxicity effects which leads to cyto-necrotic effect at longer treatment time. This study predicts the role of BBR as an inhibitor of Smo receptor, suggesting its effectiveness in hedgehog signalling during cancer treatment. It concludes that BBR through its multi-kinase inhibitory effects may be a useful replacement for lapatinib, an EGFR inhibitor which may sometimes cause drug resistance in patients.